(untitled) (Annals of Medical Research, 2024)
Aim: The equilibrium between the host immune response counter the hepatitis B virus (HBV) and the amount of viral replication is a crucial factor in the pathogenesis of HBV-associated liver disease. Tumor necrosis factor-alpha (TNF-α) is a considerable proinflammatory and immune regulatory cytokine in the pathogenesis of various inflammatory and autoimmune conditions. There is no consensus on using antiviral prophylaxis treatments in cases who have been exposed to hepatitis B but have not become chronically ill, and are thus planned to receive anti-TNF-α treatment. The aim of this study is to determine the frequency of reactivation after anti-TNF treatment in cases with isolated anti-HBc total positivity who have been exposed to hepatitis B virus. Materials and Methods: Serological HBV infection markers (HBsAg, anti-HBc IgG and anti-HBs) of 1467 adult cases who received anti-TNF therapy for the indications of various rheumatological diseases in the rheumatology and physical therapy clinics between the years 2010-2021 were retrospectively screened using the hospital’s electronic information system. Results: 140 rheumatologic disease cases who took a TNF-α inhibitor (infliximab, adalimumab, etanercept, golimumab, certolizumab) treatment were included in this study. Before the cases were started on TNF-α treatment, all cases were anti-HBc total positive, 110 were anti-HBs positive, 30 were anti-HBs negative, and 4 were HbsAg positive and HBV-DNA negative. The median pre-treatment anti-HBc total and anti-HBs values of the cases were 5.6 IU/L and 79.29 IU/L, respectively. No HBV reactivation was observed in any of the 140 cases after a median follow-up duration of 71.5 (min. 8, max. 185) months. Conclusion: In conclusion, HBV reactivation was not detected in any of the anti-HBc positive cases included in this study, which suggest that anti-HBc positive cases can be followed up with close follow-up without starting them on anti-TNF therapies and antiviral prophylaxis.